2023
DOI: 10.29333/ejmste/13272
|View full text |Cite
|
Sign up to set email alerts
|

ChatGPT: A revolutionary tool for teaching and learning mathematics

Abstract: This study aims to examine the perspectives of various stakeholders, such as students and educators, on the use of artificial intelligence in teaching mathematics, specifically after the launch of ChatGPT. The study adopts a qualitative case study approach consisting of two stages: content analysis of interviews and investigation of user experience. The first stage of the study shows that ChatGPT is recognized for its improved math capabilities and ability to increase educational success by providing users wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(79 citation statements)
references
References 44 publications
1
73
1
4
Order By: Relevance
“…It can assist in completing partially written code blocks, but lacks the execution capabilities required to produce the correct output; after all, it is a language model [8]. Likewise, ChatGPT is unable to evaluate a complex math function for a given input [9]. Thus, it is important that the user is aware of its limitations and does not entirely trust the generated output for all types of quarries.…”
Section: Introductionmentioning
confidence: 99%
“…It can assist in completing partially written code blocks, but lacks the execution capabilities required to produce the correct output; after all, it is a language model [8]. Likewise, ChatGPT is unable to evaluate a complex math function for a given input [9]. Thus, it is important that the user is aware of its limitations and does not entirely trust the generated output for all types of quarries.…”
Section: Introductionmentioning
confidence: 99%
“…An important drawback to using ChatGPT in planning mathematics lessons is that it often produces incorrect mathematical output (Wardat et al, 2023) and has been found to be limited in its ability to plan entire lessons (Gurl et al, under review). There have, however, been recent ndings that there were better student outcomes when teachers used lessons produced by ChatGPT rather than lessons prepared by teachers alone (Karaman & Goksu, 2024).…”
Section: Literature On Gai For Lesson Planningmentioning
confidence: 99%
“…Thus, it is essential that preservice teacher education programs incorporate the use of GAI chatbots so that preservice teachers (PSTs) are prepared to use these technologies in productive and useful ways as they enter the teaching profession. Although GAI such as ChatGPT can be useful, it is quite imperfect, especially in mathematics (Wardat et al, 2023), and therefore, teachers, particularly PSTs, must be re ective about the output generated by chatbots such as ChatGPT.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the absence of items concerning AI in mathematics education could be considered a limitation of the study. As AI (e.g., ChatGPT) increasingly integrates into various aspects of education, it is vital to consider its role and impact on STEM teachers' knowledge and practices (Alneyadi & Wardat, 2023;Wardat et al, 2023). Therefore, adding items concerning AI in mathematics education to TPACK scale would strengthen the scale's relevance and applicability to the current educational landscape, particularly concerning emerging technologies.…”
Section: Limitations and Future Researchmentioning
confidence: 99%